Trastuzumab deruxtecan effectively controlled recurrent ovarian large-cell neuroendocrine carcinoma with low-level HER-2 expression: a case report - Xing, Yurou; Cao, Yidan; Wu, Xin; Chen, Yue; Wang, Yongsheng (Frontiers in Oncology, 2024)
Large-cell neuroendocrine carcinoma (LCNEC) of the ovary is an extremely rare tumor with invasive clinical behavior and poor outcome. However, there is no consensus on the optimal treatment strategy. Surgery followed by chemotherapy is considered the most common therapeutic option. Here, we report a case of a 55-year-old woman with ovarian LCNEC who relapsed after radical surgery and multiple lines of therapy. The tumor lesions continued to grow, and further immunohistochemistry showed low human epidermal growth factor receptor 2 (HER2) expression. After treatment with the anti-HER2 drug trastuzumab deruxtecan (T-DXd, formerly DS-8201a), the tumor burden was significantly reduced, and the patient achieved a progression-free survival (PFS) of 4 months. Our case provides a potential treatment option for recurrent ovarian LCNEC with low-level HER2 expression.